The Importance of Positive Attitudes Toward Disability Among Future Health and Education Professionals: A Comparative Study - Luisa Gámez-Calvo; Jesús Muñoz-Jiménez; Margarita Gozalo (Education Sciences)
Understanding and embracing positive attitudes toward disability are crucial for inclusive practices. Universities play a key role in shaping these attitudes, making higher education critical for promoting inclusion and understanding diversity. This study investigates the influence of career selection and academic progression on university students’ attitudes toward disability and the associated impact on their future professional practices. A total of 446 university students from Extremadura, studying across physical activity and sports science, occupational therapy, and early childhood education, participated in this comparative study. The Spanish Attitudes Toward People with Disabilities Scale for Professionals was administered to students in their first and final years of study. The results revealed significant variations in attitudes toward disability among the different disciplines and academic years. Early childhood education and occupational therapy students exhibited more positive attitudes compared to physical activity and sports sciences students in their first year. The attitudes improved significantly across all the disciplines from the first to the final year, with notable positive changes among early childhood education and occupational therapy students. This study highlights the role of educational pathways and practical experiences in fostering positive attitudes. Tailored coursework and practical training can promote better healthcare and inclusive educational practices in future health and education professionals. Furthermore, this study highlights the need to improve the approach to competences in the analyzed university programs.